2021
DOI: 10.3354/dao03564
|View full text |Cite
|
Sign up to set email alerts
|

Analytical validation of two RT-qPCR tests and detection of spring viremia of carp virus (SVCV) in persistently infected koi Cyprinus carpio

Abstract: Spring viremia of carp virus (SVCV) ia a carp sprivivirus and a member of the genus Sprivivirus within the family Rhabdoviridae. The virus is the etiological agent of spring viremia of carp, a disease of cyprinid species including koi Cyprinus carpio L. and notifiable to the World Organisation for Animal Health. The goal of this study was to explore hypotheses regarding inter-genogroup (Ia to Id) SVCV infection dynamics in juvenile koi and contemporaneously create new reverse-transcription quantitative PCR (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…2016), and the virus has been detected by quantitative RT‐PCR in koi survivors for 167 d (Clouthier et al. 2021), collectively indicating the potential for long‐term detection of SVCV from infected fish survivors. Another potential manner whereby SVCV could persist among wild populations, which appears to have received little attention, is for invertebrates to serve as reservoirs and even vectors for this virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2016), and the virus has been detected by quantitative RT‐PCR in koi survivors for 167 d (Clouthier et al. 2021), collectively indicating the potential for long‐term detection of SVCV from infected fish survivors. Another potential manner whereby SVCV could persist among wild populations, which appears to have received little attention, is for invertebrates to serve as reservoirs and even vectors for this virus.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that would allow a rhabdovirus like SVCV, which produces acute infections with high levels of mortality that also leaves survivors immune, to persist in populations for extended periods are not well understood (Purcell et al 2012). Experimental SVCV infections of native North American fish demonstrated that survivors could maintain infections with the potential to shed virus for at least 28 d (Emmenegger et al 2016), and the virus has been detected by quantitative RT-PCR in koi survivors for 167 d (Clouthier et al 2021), collectively indicating the potential for long-term detection of SVCV from infected fish survivors. Another potential manner whereby SVCV could persist among wild populations, which appears to have received little attention, is for invertebrates to serve as reservoirs and even vectors for this virus.…”
Section: Discussionmentioning
confidence: 99%
“…It is common that not all the fish in a population that is positive for SVCV become infected or show clinical signs of infection, further complicating parameter estimates (Ahne et al., 2002 ; WOAH, 2021 ). The incubation period of SVCV in common carp is between 7 and 14 days (Ahne et al., 2002 ), the virus can be detected using RT‐PCR for at least 167 days post infection in koi; however, the maximum length of the viraemia is unknown (Clouthier et al., 2021b ). It is unclear how factors such as host species or temperature affect the transmission rate and infectious period of SVCV.…”
Section: Assessmentmentioning
confidence: 99%
“…within 30 days (Ahne et al., 2002 ). SVCV can be detected in koi carp for at least 167 days after infection (Clouthier et al., 2021b ). The maximum infectious period is unknown and could potentially be the lifetime of the animal (typically 13 to 20 years in the wild) as in the case for koi herpes virus (EFSA AHAW Panel, 2017b ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation